2021
DOI: 10.21203/rs.3.rs-454177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unpacking Future Climate Extremes and their Sectoral Implications in Western Nepal

Abstract: Existing climate projections and impact assessments in Nepal only consider a limited number of generic climate indices such as means. Few studies have explored climate extremes and their sectoral implications. This study evaluates future scenarios of extreme climate indices from the list of Expert Team on Sector-specific Climate Indices (ET-SCI) and their sectoral implications in the Karnali Basin in western Nepal. First, future projections of 26 climate indices relevant to six climate-sensitive sectors in Kar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Nepal is among the top 10 countries worldwide most affected by climatic disasters in the past two decades (Eckstein et al 2021). Extreme precipitation events, such as the numbers of heavy precipitation days and consecutive wet days, are increasing in many parts of the country, especially in the western half (Karki et al 2017;Chapagain et al 2021), and warm days and nights are occurring more frequently across the country (DHM 2017). Previous studies have observed increasing trends in the frequency of climatic disasters and mortality from climatic disasters in Nepal (Petley et al 2007;Aryal 2012;Elalem and Pal 2015;Aksha et al 2018;Adhikari and Tian 2021;MoFE 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nepal is among the top 10 countries worldwide most affected by climatic disasters in the past two decades (Eckstein et al 2021). Extreme precipitation events, such as the numbers of heavy precipitation days and consecutive wet days, are increasing in many parts of the country, especially in the western half (Karki et al 2017;Chapagain et al 2021), and warm days and nights are occurring more frequently across the country (DHM 2017). Previous studies have observed increasing trends in the frequency of climatic disasters and mortality from climatic disasters in Nepal (Petley et al 2007;Aryal 2012;Elalem and Pal 2015;Aksha et al 2018;Adhikari and Tian 2021;MoFE 2021).…”
Section: Introductionmentioning
confidence: 99%